Pengembangan Permainan Edukasi Pengenalan Chord Gitar Berbasis Virtual Reality Dengan Menggunakan Myo Armband - Aditya Yudha Agung N; Tri Afirianto; Issa Arwani (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
In learning the guitar, it is necessary to know the basic chords that can be learned through books or the internet. However, the use of print media does not provide real experience to students. Therefore we need an interactive learning media that can provide real experiences to students. By using virtual reality and Myo Armband this research combines the two technologies into interactive learning games so they can provide real experiences to their students. The system built using the MDA Framework, describing the mechanics, dynamics and aesthetics that exist in the game system. The system is tested using the System Usability Scale (SUS) and Task Completion Rate to test User Experience (UX) of the system, Black Box testing to validate functions in the system and pre-test - post-test testing to test the influence of the game on increasing understanding of material. The results showed that the value of the SUS test was 67.5%, which number did not meet the SUS standard of 68%. The black box testing test results get a 100% valid result which indicates that the functional system of the game has been running correctly. The results of task completion testing give an average yield of 91.43% with a standard task completion of 78% which indicates that this system is good in terms of its effectiveness. The pre-test and post-test tests get an average result for the pre-test of 70 and a post-test of 90. From the two values, there are 20 equalizations which indicate that there is an increase in player understanding in other words the game has succeeded as an interactive learning media.